Legal flows: contributions of exiled lawyers to the concept of "crimes against humanity" during the Secon World War - Lingen, Kerstin von (Modern intellectual history, 2018)
This article addresses the normative framework of the concept of “crimes against humanity” from the perspective of intellectual history, by scrutinizing legal debates of marginalized (and exiled) academic-juridical actors within the United Nations War Crimes Commission (UNWCC). Decisive for its successful implementation were two factors: the growing scale of mass violence against civilians during the Second World War, and the strong support and advocacy of “peripheral actors,” jurists forced into exile in London by the war. These jurists included representatives of smaller Allied countries from around the world, who used the commission's work to push for a codification of international law, which finally materialized during the London Conference of August 1945. This article studies the process of mediation and the emergence of legal concepts. It thereby introduces the concept of “legal flows” to highlight the different strands and older traditions of humanitarian law involved in coining new law. The experience of exile is shown to have had a significant constitutive function in the globalization of a concept (that of “crimes against humanity”).
Gesehen am 02.09.2019